PERANCANGAN PROMOSI RANDANG LOKAN CANI WIN DALAM MEDIA SOSIAL - Ranggi Septiawan; m.nasrul kamal (Universitas Negeri Padang, 2020)
Randang Lokan Cani Win is a business that operates in the field of food from the type of lokan, having its address in the area of Jorong Padang Halaban, Nagari Sasak, Sasak Ranah Pasisie District, West Pasaman Regency. Founded on August 14, 2017 until now.The selection of Rkan Loan Cani Win Promotion in Social Media as this final project aims to produce an effective and efficient promotional design in accordance with the advantages of social media promotion that is able to reach broad targets. In addition, with this promotion, it will later be able to show the Loan Cani Win Randang Randang so that it can optimize in knowing the Loan Cani Win Randang. SWOT is a method used in collecting data through observation, interviews, and documentation. Then proceed with the method of data analysis using SWOT analysis (strength, weakness, opportunities, threats). Then conclude the data analysis and take a creative approach (the main and supporting media). The design of the Randang Lokan Cani Win Promotion in Social Media the author displays verbal and visual messages for the audience who see this promotion.The design of this promotion is expected to create a good positioning. In addition, it is expected to be able to attract the attention of the target audience, especially people who come to the city of West Pasaman, considering that social media-based promotional media is a media that is very likely and has a great influence in increasing promotion coupled with supporting media such as T-shirts, Xbanner, Stickers, Packaging, Wall Clock,, Flag Chain and Name Cards.Keywords: Design, Randang Lokan Cani Win, Social Media.